THE REASONS FOR CIVIL DISOBEDIENCE IN DEMOCRATIC SOCIETIES (Andamios, Revista de Investigación Social, 2009)
The aim of this paper is to show that, faced with a widening lack of trust in political parties, in popular leaders and in public servants, civil disobedience becomes a crucial arm in the symbolic arsenal that of democratic states of law. Public disobedience triggers two legitimating principles in a democratic order: the people’s sovereignty and recognition among all of the right to have rights. It helps, for this very reason, to keep safe and expand rights, on the one hand, and to broaden the democratic horizon, on the other.
Keywords: Civil disobedience; democracy; civil rights; Habermas; Dworkin